Experimental study on bottom boundary layer beneath solitary wave - Winarta, Bambang; Nadiatul Adilah, Ahmad Abdul Ghani; Tanaka, Hitoshi; Yamaji, Hiroto; Mohammad Fadhli, Ahmad (Asian Research Publishing Network (ARPN), 2016)
A tsunami as long wave and an oscillatory wave moves into shoaling water have behavior similar to solitary wave and therefore comprehension on its bottom boundary layer characteristics come to be essential key on near-shore sediment transport modeling. In the present study, the hydraulics phenomena of solitary wave are studied in deep through experiments utilizing a closed conduit generation system. This result was examined by analytical and numerical laminar solution. Moreover, wave friction factor is discussed based on the present laboratory experiment and previous studies of (Sumer et al., 2010); (Vittory and Blondeaux, 2011, 2012). As conclusions, in-consistent critical Reynolds number was found for solitary wave case. This observable fact is distinct difference with sinusoidal wave case which has consistency in critical Reynolds number. As a main conclusion that a new generation system proposed in the present study will be able and applicable to shore up an experiment on sediment transport induced by solitary wave.